2007
DOI: 10.1002/app.26189
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl‐terminated butadiene acrylonitrile rubber/epoxy polymer alloys as damping adhesives and energy absorbable resins

Abstract: Carboxyl-terminated butadiene acrylonitrile (CTBN) liquid rubber/epoxy (diglycidyl ether of bisphenol-A: DGEBA) / diamino diphenyl methane (DDM) resins, in which CTBN was 60 wt % as the major component, were formulated to evaluate the damping and adhesive properties. In cases where acrylonitrile (AN) was 10$18 mol % as copolymerization ratio in CTBN, the blend resins showed micro-phase separated morphologies with rubber-rich continuous phases and epoxy-rich dispersed phases. The composite loss factors (Z) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…Many research works have been carried out in the dynamic characteristics of composite material [1][2][3][4][5][6]. Biggerstaff J.M and Kishi.H et al proved that through toughening of polymer matrix the damping effect can be improved [7,8].Senthil Kumar et.al proved that an increase in fibre content increases the mechanical and damping properties in natural composites [9]. XuLe et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Many research works have been carried out in the dynamic characteristics of composite material [1][2][3][4][5][6]. Biggerstaff J.M and Kishi.H et al proved that through toughening of polymer matrix the damping effect can be improved [7,8].Senthil Kumar et.al proved that an increase in fibre content increases the mechanical and damping properties in natural composites [9]. XuLe et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Kishi et al [5] found that though the CTBN/DGEBA/DDM (diamino diphenyl methane) resins indicated high damping performance and high adhesive strength to aluminum substrates, there was always loss of strength of the materials accompanied with the improvement of toughness. The work of Ratna and Banthia [6] showed that the tensile strength and flexural strength of the epoxy resins modified by carboxyl terminated poly(2-ethylhexyl acrylate) decreased rapidly with increase of the rubber.…”
mentioning
confidence: 99%
“…All the components (liquid rubber, epoxy oligomer, and diamine) were found to react with one another to generate a covalent bonded network, and so the product was not technically an IPN. In a previous study, CTBN/DGEBA/DDM networked polymer blends showed good adhesive and damping properties over a wide range of temperatures . These desirable characteristics were achieved by selecting components that were compatible with one another.…”
Section: Introductionmentioning
confidence: 96%
“…Our group has previously studied polymer blends consisting of a liquid reactive rubber (carboxyl‐terminated butadiene acrylonitrile rubber (CTBN)), an epoxy resin (diglycidyl ether of bisphenol‐A (DGEBA)), and an aromatic diamine (diamino diphenyl methane (DDM)) . Although CTBN is known to act as a toughening modifier in epoxy resins, in our prior work, it was used as the major component (at 60 wt%) of the polymer blends . All the components (liquid rubber, epoxy oligomer, and diamine) were found to react with one another to generate a covalent bonded network, and so the product was not technically an IPN.…”
Section: Introductionmentioning
confidence: 99%